Certain bacteria that induce biological ice nucleation are suspected to play an important role in condensation and ice nuclei formation in clouds. Those bacteria can produce biological ice nucleator1, which is a protein and usually found on leaf surface and air. Most studies on INA bacteria were conducted in subtropical areas. In this study, INA bacteria were isolated from rain-water and air between March to May 2008 from Jakarta, Bogor, Bekasi, Tangerang, and Depok. The percentage of INA bacter - . STEPHANIE; DIANA ELIZABETH WATURANGI (Bogor Agricultural University, Indonesia, 2011)
Certain bacteria that induce biological ice nucleation are suspected to play an important role in condensation and ice nuclei formation in clouds. Those bacteria can produce biological ice nucleator1, which is a protein and usually found on leaf surface and air. Most studies on INA bacteria were conducted in subtropical areas. In this study, INA bacteria were isolated from rain-water and air between March to May 2008 from Jakarta, Bogor, Bekasi, Tangerang, and Depok. The percentage of INA bacteria from rainfall for those area are 19.4, 18.7, 5.3, 2.2, and 6.4% respectively, while percentage for air are 9.5, 6.5, 0, 2.7, and 1.8%. The highest incidence of INA bacteria were from rain-water and air found in sample from Jakarta and then followed by the samples from Bogor. It was shown that the percentage of INA bacteria from rain-water was higher than air for all of the samples from different areas. The isolate from Jakarta (isolate A32) which had the highest activity for ice nucleation, with the temperature classification at -2.7 oC, revealed 100% similarity with Pantoea sp. The presence of INA bacteria in rain-water and air might play an important role in nucleation process which is required for rainfall induction.